PENGARUH PENGENDALIAN INTERN AKUNTANSI, PEMANFAATAN TEKNOLOGI INFOMASI DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KEANDALAN DAN KETEPATAN WAKTU PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus di OPD Kota Surakarta) - Octalia Risha Susilawati; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The purpose of this research is to examine the effect of accounting internalcontrols, theause of information technology, and human resources capacity on thereliability and timeliness of financial reporting in local governments. The objectof this research was the staff accounting of the OPD in Surakarta City. Type ofdata uses in this research is primary data and the population was 33 OPDD inSurakarta City. The data obtained by quetionnaires. The data were analyzed byusing multiple linear regression analysis. Technique of data analysis use a classicassumptionatest, multiplealinear regression analysis, t-test, F-test and coefficientof determination(R2). Results of this research indicate that accounting internalcontrol, the use of information technology and human resources capacityoversight a positive significant influence on the reliability and timeliness offinancial reporting in thealocal governments in the Surakarta City.